1966
DOI: 10.1149/1.2423812
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Silicon Carbide at 1150° to 1400°C and at 9 × 10[sup −3] to 5 × 10[sup −1] Torr Oxygen Pressure

Abstract: A kinetic study was made of the oxidation of high-purity silicon carbide using a dynamic-type reaction system. Two types of oxidation behavior were found. Passive oxidation occurred for conditions where silica films were formed on the surface. Active oxidation occurred for conditions where volatile silicon monoxide was formed. The transition conditions between the two types of oxidation were studied as a function of oxygen pressure and temperature. The transition temperatures and pressures were related to ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 12 publications
3
28
1
Order By: Relevance
“…Compared with Gulbransen's research [17], only the reaction shown in Equation (2) occurred in this study. The oxygen molecule was the diffusion unit [18].…”
Section: The Reaction Between Sic and O 2 Is Shown In Equationscontrasting
confidence: 73%
See 1 more Smart Citation
“…Compared with Gulbransen's research [17], only the reaction shown in Equation (2) occurred in this study. The oxygen molecule was the diffusion unit [18].…”
Section: The Reaction Between Sic and O 2 Is Shown In Equationscontrasting
confidence: 73%
“…For the critical pore, the relationship between the two abovementioned factors is the key to describing Q in and Q m . When the temperature is 1200 • C, the mean free path of the oxygen molecule, as calculated by Equation (17) [27], is 3.2307e −6 m.…”
Section: The Reaction Between Sic and O 2 Is Shown In Equationsmentioning
confidence: 99%
“…Two main oxidation modes have been observed in presence of oxygen, depending on its partial pressure, temperature and mass flow velocity. At very high temperatures and low oxygen partial pressure, or very high velocities (over 100 m/s), the so-called active oxidation is dominant and the material is gradually consumed by the following reactions [8][9][10]:…”
Section: Introductionmentioning
confidence: 99%
“…(3) [20] and (4) [21] is SiO 2 layer. The relationship between the SiO 2 layer thickness and oxidation time satisfies the asymptote rule [22].…”
Section: Surface-oxidation Modificationmentioning
confidence: 99%